Contribuição Winnicottiana ao Modelo de Atendimento no Programa de Internação na Fundação Casa - SP - Lima, Danielli Do Lago Hyppolito De [UNIFESP] (2019)
The objective of this research was to analyze how the application of the Winnicottian precepts in the implementation of the socio-educational measure of hospitalization in one of the Service Centers of the CASA-SP Foundation is made through the understanding and meaning given by the teenager and the servants. The historical background of the construction of policies aimed at assisting juvenile offenders and the challenges faced in the search for the guarantee of rights, the current guidelines of the institution and the specific theoretical framework that guides the practice of this Service Center were the pillars of the study, directing the analysis of the content brought by adolescents and the team that develops the work. The profile of the adolescents and the characteristics of the family composition were relevant elements for the composition of the research, as well as the current institutional scenario, allowing the contextualization and a deepening of the analysis. To do so, the method adopted was the descriptive study, with qualitative orientation, proposing as participants the adolescents and professionals who develop the interventions, so that the evaluation considered the perspectives of these two sides, in the execution of this model, through individual interviews with the young people and focus group with the team, content this categorized, once we opted for categorial analysis of the material. The results pointed out convergences between the guidelines and Winnicottian precepts, enabling the practice of care adopted at this Center to be a potential space, admittedly favorable, both by the adolescents assisted, and by the professionals, to personal maturation.